2002
DOI: 10.2166/wst.2002.0531
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous micro-organisms observed in industrial activated sludge plants

Abstract: As part of the EU-sponsored MACOBS (Monitoring and Control of Bulking Sludge through Molecular Probe Assays) project, the size and the composition of the filamentous population in 73 industrial activated sludge plants, were investigated. The inventory included plants in Denmark, Germany, Italy and The Netherlands. Large filamentous populations were present in about 60% of the plants, which means that bulking of activated sludge, which is no longer a serious problem in modern domestic nutrient removal plants, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 7 publications
(3 reference statements)
0
59
0
4
Order By: Relevance
“…Several different filament morphotypes have been described from systems treating domestic and industrial wastes (17,18) but, in the absence of pure cultures, many of these have never been characterized sufficiently to resolve their taxonomy or provide them with valid names. Hence, they are often still referred to as numerical types persisting from the study of Eikelboom (18).…”
mentioning
confidence: 99%
“…Several different filament morphotypes have been described from systems treating domestic and industrial wastes (17,18) but, in the absence of pure cultures, many of these have never been characterized sufficiently to resolve their taxonomy or provide them with valid names. Hence, they are often still referred to as numerical types persisting from the study of Eikelboom (18).…”
mentioning
confidence: 99%
“…The evaluation of activated sludge parameters was performed according to the procedures described by Eikelboom and FijaƂkowska [15][16]. The qualitative species composition of activated sludge was assessed from microscopic observations (magnification 10x, 20x, and 40x) of slides treated with a vital stain.…”
Section: Activated Sludgementioning
confidence: 99%
“…The filamentous bacteria present in WWTP were morphologically identified and the filament characteristics were determined using the Eikelboom's classification system (Table 1) (Eikelboom and Geurkink, 2000;Eikelboom and van Buijsen, 1983). Referring to morphological and color characteristics of the filaments (Jenkins et al, 2004), the Gram staining and Neisser staining were respectively performed as described by Adamse (1970) and Gurr (1965).…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…More than 30 different filament morphotypes have been described in activated sludge systems treating primarily municipal wastewater (Eikelboom, 1975(Eikelboom, , 2000 and many more are encountered in industrial treatment plant communities (Eikelboom, 2006;Eikelboom and Geurkink, 2002). Several global surveys have shown that Candidatus Microthrix parvicella (hereinafter referred to as M. parvicella) is most frequently responsible for the problems of solid-liquid separation in bulking and foaming (Jenkins et al, 2004;Martins et al, 2004;Wanner, 1994).…”
Section: Introductionmentioning
confidence: 99%